Life cycle cost analysis of wastewater treatment: A systematic review of literature - Ilyas, Muhammad; Kassa, Freselam Mulubrhan; Mohd Ridzuan, Darun (Elsevier, 2021)
The last two decades have witnessed a substantial increase in literature on the life cycle costing of Wastewater treatment. Lack of commonly agreed methodology of life cycle costing resulted in the use of different frameworks and methodologies. Methods and approaches in conducting life cycle cost analysis are also evolving, and a gradual shift from conventional to environmental and societal life cycle costing is witnessed in the last decade. However, a detailed systematic review of methods and approaches of life cycle costing in Wastewater treatment is still lacking. A comprehensive and systematic review provides an opportunity to record existing development in the field and identify areas where more research is needed. For this purpose, this paper systematically reviews the literature on the life cycle cost analysis of wastewater treatment, focusing on purpose, approach, methodology, integration with life cycle assessment, cost estimation, and dealing with uncertainty. The analysis of 83 identified case studies indicated that most of the studies are conducting for affordability and comparative analysis. A gradual shift from conventional to environmental life cycle cost analysis is also observed. 44% of the studies are integrated with Life cycle assessment through different methods. However, in these integrated studies, life cycle cost analysis is used as a secondary tool to supplement the life cycle assessment. Analytical and statistical methods are generally used for cost estimation. Deterministic methods are most common to deal with uncertainties. Based on the comprehensive review of case studies, it is suggested that future research should aim at developing a framework for life cycle cost analysis that could consider and allocate all costs associated with the Wastewater treatment process.